Direct demonstration of three different states of the pancreatic cholecystokinin receptor. - Talkad, V D (1994)
We used rat pancreatic acini as well as COS-7 cells transfected with the cloned pancreatic cholecystokinin (CCK) receptor and measured the abilities of CCK octapeptide (CCK-8) and L-364,718 (a CCK receptor antagonist) to inhibit binding of 125I-labeled CCK-8 (125I-CCK-8) and [3H]L-364,718. With pancreatic acini 125I-CCK-8 bound to two different states of the CCK receptor. The high-affinity state (1% of the receptors) had a Kd for CCK-8 of 985 pM and the low-affinity state (19% of the receptors) had a Kd for CCK-8 of 30 nM. [3H]L-364,718 bound to low-affinity receptors and to a previously unrecognized very-low-affinity state (80% of the receptors) having a Kd for CCK-8 of 13 microM. L-364,718 had the same affinity (Kd 3 nM) for each of the three different states of the CCK receptor. Similar measurements using transfected COS cells also identified three different states of the CCK receptor, with the very-low-affinity state being the most abundant. Thus, the ability of the CCK receptor to exist in three different states is an intrinsic property of the CCK receptor molecule itself.